2012
DOI: 10.1021/jo300141z
|View full text |Cite
|
Sign up to set email alerts
|

Nucleofugality and Nucleophilicity of Fluoride in Protic Solvents

Abstract: A series of p-substituted benzhydryl fluorides (diarylfluoromethanes) were prepared and subjected to solvolysis reactions, which were followed conductometrically. The observed first-order rate constants k(1)(25 °C) were found to follow the correlation equation log k(1)(25 °C) = s(f)(N(f) + E(f)), which allowed us to determine the nucleofuge-specific parameters N(f) and s(f) for fluoride in different aqueous and alcoholic solvents. The rates of the reverse reactions were measured by generating benzhydrylium ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 61 publications
0
42
0
Order By: Relevance
“…Because of the fast background reaction of the carbocation with the solvent (10 5 s À1 ), however, the reaction of the carbocation with the fluoride anion can only be followed by laser flash photolysis using high concentrations of fluoride anions. [45] Rate constants for the reactions of some nucleophiles, for example, tertiary amines or dialkylsulfides, with carbocations cannot be studied with conventional methods at all. This is the case when the reactions of these nucleophiles with stabilized carbocations are thermodynamically unfavorable, while their reactions with less stabilized carbocations are very fast.…”
Section: When Is the Use Of Laser Flash Photolysis Advantageous?mentioning
confidence: 99%
See 4 more Smart Citations
“…Because of the fast background reaction of the carbocation with the solvent (10 5 s À1 ), however, the reaction of the carbocation with the fluoride anion can only be followed by laser flash photolysis using high concentrations of fluoride anions. [45] Rate constants for the reactions of some nucleophiles, for example, tertiary amines or dialkylsulfides, with carbocations cannot be studied with conventional methods at all. This is the case when the reactions of these nucleophiles with stabilized carbocations are thermodynamically unfavorable, while their reactions with less stabilized carbocations are very fast.…”
Section: When Is the Use Of Laser Flash Photolysis Advantageous?mentioning
confidence: 99%
“…In 1972, Ivanov et al reported the flash photolytic generation of methoxysubstituted tritylium ions from the corresponding triarylacetonitriles Scheme 3. Reaction of the di(p-anisyl)methyl cation with fluoride in water [45] 0.0 t / µs Figure 1. Decays of the absorbance of the bis[4-(dimethylamino)phenyl] methyl cation at 605 nm after the irradiation of the substituted benzhydryl triphenylphosphonium salt (1 Â 10 À5 M) in the presence of different concentrations of 1,1-dimethyl hydrazine in CH 3 CN at 20 C [51] (Scheme 5(b)).…”
Section: Historic Perspectivementioning
confidence: 99%
See 3 more Smart Citations